Influence of raindrop size distribution variations on the rain specific attenuation coefficients - J, Nyamjav; M, Batpurev; S, Jamiyan (Scientific transaction of the National University of Mongolia. Physics, 2022)
The raindrop size distribution is one of main term to evaluate microwave attenuation due to rainfall. In this paper, the lognormal distribution is introduced to represent the raindrop-size distribution based on the measurement performed at the Chungnam National University. Since the distribution parameters are strongly scattered around the fitted value, we developed a new statistical model for the lognormal distribution parameters. Based on the new statistical model for raindrop size distribution parameters we have estimated influence of raindrop size distribution variations on the rain specific attenuation coefficients.